General motors: A financialized account of corporate behaviour 1909–1940. Issue 4 (1st December 2016) - Maielli, Giuliano; Haslam, Colin
Abstract: This paper constructs an alternative account of resource stewardship at General Motors (GM) during the period 1909–1940. Alfred Chandler employed GM in his text 'Strategy and Structure' to explain the development of the modern corporation. This understanding can be employed to contrast an 'old-economy' with a 'new-economy' financialized corporate business model. In this paper we find that many elements of the financialized firm were present in the early history of GM's development. Our analysis reveals the financialization of a non-financial corporation and how this influenced corporate behaviour and impacted on financial performance at GM during the period 1909–1940.